Myocardial fibrosis induced by nonylphenol and its regulatory effect on the TGF-β1/LIMK1 signaling pathway - Guo, Mei; Xu, Jie; Long, Xianping; Liu, Weichu; Aris, Ahmad Zaharin; Yang, Danli; Luo, Ya; Xu, Yuzhu; Yu, Jie (Elsevier, 2024)
Objective: We here explored whether perinatal nonylphenol (NP) exposure causes myocardial fibrosis (MF) during adulthood in offspring rats and determined the role of the TGF-β1/LIMK1 signaling pathway in NP-induced fibrosis in cardiac fibroblasts (CFs). Methods and results: Histopathology revealed increased collagen deposition and altered fiber arrangement in the NP and isoproterenol hydrochloride (ISO) groups compared with the blank group. Systolic and diastolic functions were impaired. Western blotting and qRT-PCR demonstrated that the expression of central myofibrosis-related proteins (collagens Ι and ΙΙΙ, MMP2, MMP9, TGF-β1, α-SMA, IL-1β, and TGF-β1) and genes (Collagen Ι, Collagen ΙΙΙ, TGF-β1, and α-SMA mRNA) was upregulated in the NP and ISO groups compared with the blank group. The mRNA-seq analysis indicated differential expression of TGF-β1 signaling pathway-associated genes and proteins. Fibrosis-related protein and gene expression increased in the CFs stimulated with the recombinant human TGF-β1 and NP, which was consistent with the results of animal experiments. According to the immunofluorescence analysis and western blotting, NP exposure activated the TGF-β1/LIMK1 signaling pathway whose action mechanism in NP-induced CFs was further validated using the LIMK1 inhibitor (BMS-5). The inhibitor modulated the TGF-β1/LIMK1 signaling pathway and suppressed the NP-induced increase in fibrosis-related protein expression in the CFs. Thus, the aforementioned pathway is involved in NP-induced fibrosis. Conclusion: We here provide the first evidence that perinatal NP exposure causes myocardial fibrosis in growing male rat pups and reveal the molecular mechanism and functional role of the TGF-β1/LIMK1 signaling pathway in this process.